2022
DOI: 10.4018/978-1-6684-2472-8.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Criteria Used to Evaluate Renewable Energy Sources in Turkey With Fuzzy SWARA

Abstract: The aim of this study is to determine the criteria used in the evaluation of renewable energy resources with the extremely high strategic importance that Turkey has and to find their degree of importance. For this purpose, an application has been made to find which criteria come to the fore and the weights of these criteria in order to evaluate Turkey's renewable energy resources. Five main criteria (technical, economic, environmental, social, and political) and a total of 22 sub-criteria related to these crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In contrast to the SWARA method, the PIPRECIA method doesn't require criteria to be ranked based on expected significance prior to the use. Although less commonly used than the SWARA method, PIPRECIA has been applied in various scenarios such as assessing customer satisfaction (Stanujkic et al, 2019), personnel selection based on a novel grey PIPRECIA and grey OCRA methods (Ulutaş et al, 2020), the evaluation of the hotel websites (Stanujkic et al, 2021a), selection of renewable energy sources with the plithogenic PIPRECIA method (Ulutaş & Topal, 2022), green supplier's selection (Puńka, 2022), and evaluating renewable energy sources using fuzzy logic (Keleş et al, 2022). During the application of the PIPRECIA method, some respondents have suggested that it would be simpler to always compare the significance of the criteria with the first criterion.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the SWARA method, the PIPRECIA method doesn't require criteria to be ranked based on expected significance prior to the use. Although less commonly used than the SWARA method, PIPRECIA has been applied in various scenarios such as assessing customer satisfaction (Stanujkic et al, 2019), personnel selection based on a novel grey PIPRECIA and grey OCRA methods (Ulutaş et al, 2020), the evaluation of the hotel websites (Stanujkic et al, 2021a), selection of renewable energy sources with the plithogenic PIPRECIA method (Ulutaş & Topal, 2022), green supplier's selection (Puńka, 2022), and evaluating renewable energy sources using fuzzy logic (Keleş et al, 2022). During the application of the PIPRECIA method, some respondents have suggested that it would be simpler to always compare the significance of the criteria with the first criterion.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the relationships among criteria in the decision-making of RES investment, analytic hierarchy process (AHP) (Ulewicz et al, 2021;Karatop et al, 2021;Sedghiyan et al, 2021), stepwise weight assessment ratio analysis (SWARA) (Dinçer et al, 2022;Keleş et al, 2022;Rani et al (2021), and decision-making trial and evaluation laboratory (DEMATEL) technique Li et al al., 2022;Xie et al, 2021;Zhang and Deng, 2019) are frequently applied. Among these methods, AHP only takes into account the hierarchy structure of the criteria; SWARA only considers the hierarchical priorities of the experts.…”
Section: Introductionmentioning
confidence: 99%